Conformal MIMO loop antenna for ingestible capsule applications. Issue 23 (1st November 2017) - Xu, Li‐Jie; Li, Bo; Zhang, Ming; Bo, Yaming
Abstract : An MIMO antenna consisting two loop elements is presented at 2.45 GHz industrial, scientific and medical band. The two elements are attached on the inner surface of the capsule, so that inner capsule space is saved to its maximum extent. Additionally, by orthogonally placing the two elements at bottom and side of the capsule, different polarisation directions are achieved; therefore, resulting in good isolation without introducing additional decoupling structures. Furthermore, communication link of the MIMO antenna with outside dipole is evaluated, revealing reliable communication performance. Finally, simulation results are validated by experimental results with good agreement.